2020
DOI: 10.1039/d0ob00272k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, properties and reactivity of BCl2 aza-BODIPY complexes and salts of the aza-dipyrrinato scaffold

Abstract: Conversion of F-aza-BODIPYs to Cl-aza-BODIPYs enables facile substitution at boron using aryl Grignard reagents as well as controlled deborylative deprotection to give the parent azadipyrrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Presumably, the reaction of BODIPY 1 in the presence of boron trichloride proceeds via either the formation of a boronium cation intermediate, 41 followed by the nucleophilic attack of the amino acid carboxylate group on boron to produce product A , or via the in situ formation of a Cl 2 -BODIPY intermediate 43 45 leading to products B and C .…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, the reaction of BODIPY 1 in the presence of boron trichloride proceeds via either the formation of a boronium cation intermediate, 41 followed by the nucleophilic attack of the amino acid carboxylate group on boron to produce product A , or via the in situ formation of a Cl 2 -BODIPY intermediate 43 45 leading to products B and C .…”
Section: Resultsmentioning
confidence: 99%
“…For example, formation of the Cl-aza-BODIPY 36 occurs through stepwise halogen exchange and a mixed halogen BODIPY intermediate featuring a -BClF unit. 86 Cl-aza-BODIPYs such as 36 were found to be unstable after a few days of exposure to air, decomposing to the aza-dipyrrin HCl salts. The utility of the Cl-aza-BODIPY scaffold, as contained within the subphthalocyanine motif, 87 extends to substitution at boron under mild conditions through treatment with aryl Grignard reagents, courtesy of the lability of the B-Cl bond.…”
Section: Discussionmentioning
confidence: 99%
“…7 In 2020, Thompson et al reported a series of diaryl-substituted aza-BODIPYs on the boron atom generated by the reaction of BCl 2 -aza-BODIPY complexes with a Grignard reagent, and the maximum absorption wavelengths of diphenyl-substituted aza-BODIPYs with low quantum yield ( Φ f < 0.01) were also found to be hypochromatically shifted by 35 nm. 8 Until now, only the synthesis and simple optical properties of aryl-substituted aza-BODIPYs have been investigated, and it is therefore urgent that we explore the potential application of aryl-substituted aza-BODIPYs. We noticed weak fluorescence of diphenyl-substituted aza-BODIPY (DPh-azaBODIPY) on the boron centre, which provides favorable conditions for PTT, according to the Jablonski diagram.…”
Section: Introductionmentioning
confidence: 99%